VD_FINDINFO Pron / 2012 / 261 vom 6. Dezember 2012 - VD Tribunal cantonal (2012)
DÉLAI DE RECOURS, RETARD INJUSTIFIÉ, CASE POSTALE, LA POSTE, CLAUSE CONTRACTUELLE | 273 CC, 420 al. 2 CC, 464 CPC, 489 CPC